2019
DOI: 10.1093/ve/vez045
|View full text |Cite|
|
Sign up to set email alerts
|

On the stability of sequences inserted into viral genomes

Abstract: Viruses are widely used as vectors for heterologous gene expression in cultured cells or natural hosts, and therefore a large number of viruses with exogenous sequences inserted into their genomes have been engineered. Many of these engineered viruses are viable and express heterologous proteins at high levels, but the inserted sequences often prove to be unstable over time and are rapidly lost, limiting heterologous protein expression. Although virologists are aware that inserted sequences can be unstable, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 145 publications
(197 reference statements)
1
35
0
Order By: Relevance
“…However, the loss of PDS inserts still occurred when this FoMV vector was used to silence PDS in maize [ 34 ]. Therefore, the stability of sequences inserted into viral genomes is regard as a surprisingly complex problem involved in the genome characteristics, the host environment and the demography of a virus population [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the loss of PDS inserts still occurred when this FoMV vector was used to silence PDS in maize [ 34 ]. Therefore, the stability of sequences inserted into viral genomes is regard as a surprisingly complex problem involved in the genome characteristics, the host environment and the demography of a virus population [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study confirmed these results and found significant structural differences between rNDV-H5 and the parental LaSota NDV. Because the H5 gene is inserted upstream of the 3’ end of the genome of the rNDV-H5 construct, between phosphoprotein and matrix genes, the level of expression of downstream F and HN could be impacted and reduced [ 46 , 47 ]. However, the investigation of both surface glycoproteins distribution demonstrated a higher expression of HN and a lower expression of F by rNDV-H5 when compared to parental NDV LaSota, although HN is positioned more distally than F in the NDV genome.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, PCR analysis of the three successive passages (P1-P3) and the OBs obtained after injection of BVs at P0 in larvae revealed that only the product corresponding to Bac-polh-Ø was present, which implies the complete loss of these genes. It has been shown that genes inserted in the genomes of recombinant viruses, to express heterologous proteins at high levels, often prove to be unstable over time and can be rapidly lost [40]. This loss might be particularly rapid when the inserted gene encodes a protein that is deleterious for the virus.…”
Section: Discussionmentioning
confidence: 99%